Practices leading to information literacy development among Nigerian undergraduates - K., Kiran; Jinadu, Iliasu; Kiran, K. (Malaysian Journal of Library and Information Science, 2016)
This study examines the practices of academics, as employees, to understand how information literacy skills (IL) evolve in the workplace (college context). The study uses the practice approach, relying on qualitative case study. Data are collected through in-depth interviews and nonparticipatory observations from nine (9) purposely selected Heads of Departments in a college of education in Nigeria. The findings highlight eight (8) practices through which the academics engage themselves and their undergraduates; and identify the information skills that may evolve from such practices. The study concludes that academics’ practices may nurture IL skills to solve information seeking problems in academia as well as students’ future workplace. The study reveals the need for future tracer studies that could investigate how other factors hinder or facilitate the performance of graduates (employees) in the workplace.